Discovery of Sex-Determining Genes in Portunus trituberculatus: A Comparison of Male and Female Transcriptomes During Early Developmental Stages - Zhang, Wen; Lv, Jianjian; Lan, Weikang; Gao, Baoquan; Liu, Ping (Frontiers in Marine Science, 2022)
Portunus trituberculatus is one of the main mariculture crabs of high economic value. To identify genes involved in sex determination, we first performed sex-specific transcriptome sequencing at six larval development stages using a DNA/RNA co-extraction method. A total of 907,952,938 and 828,774,880 reads were obtained from female and male crabs, respectively. 2,379 differentially expressed genes (DEGs) were found between females and males, and were mainly enriched in DNA replication, folate biosynthesis, and retinol metabolism pathways. Furthermore, expression patterns of genes in the sex-determining region (SD) were analyzed based on the transcriptome data, and one Dmrt gene (PtDMY) was found to be exclusively expressed in males during early developmental stages. Notably, some known sex-related genes, including IAG, Dmrt11E, DmrtB1, and DmrtC2 were significantly down-regulated after knocking down PtDMY. Our results suggested that PtDMY is involved in sex determination and may be one of the key upstream regulators of the sex determination pathway. In addition, the massive volume of transcriptome data obtained in this study provided an important basis for the systematic study of sex determination mechanisms in P. trituberculatus.